DETERMINATION OF Cr(VI) BY USING CHITOSAN-1,5- DIPHENYL CARBAZIDE RESIN MODIFIED AT THE PRECONCENTRATION SYSTEM WITH COLUMN METHOD - AMAN SENTOSA PANGGABEAN; BOHARI YUSUF (International Journal of Pharma and Bio Sciences, 2015)
A chelating resin of chitosan-1,5-diphenylcarbazide modified with the alginate salts and utilization as a filler material column has been synthesized and the sorption properties have been investigated for preconcentration and determination of Cr(VI) at trace levels The optimal composition of the formation of Ca-alginate-chitosan-1,5-diphenylcarbazide microcapsules were 1% Na-alginate, 0.1M CaCl2 and 0.6 g resin. The retention capacity of resin modified was 2.2124 mg Cr (VI) /g resin at optimum pH 4-6. The analytical performance this method is good which are shown by the limit of detection was 1.14 µg/L and the reproducibility level shown by the percentage of the coefficient variance was 1.9563 %. This method was applied for Cr(VI) determination in river water samples collected from Karang Mumus and Mahakam Rivers, East Kalimantan, Indonesia.